Game dalam Upaya Menaikkan Citra Perpustakaan di Kalangan Generasi Strawbery - Rusmiatiningsih, Rusmiatiningsih; Rizkyantha, Okky (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
This is a new author guidelines and article template of Tik Ilmeu: Jurnal Ilmu Perpustakaan dan Informasi since the year 2017 publication. Article should be started by the title of the article followed by the author's name and affiliation address and abstract. This abstract section should be of size 11 pt and number of words 150-200. Special for the abstract section, please use left margin of 35 mm, right margin of 30 mm. The single spacing should be used between lines in this article. If the article is written in Indonesian, the abstract should be typed in Indonesian and English. Meanwhile, if the article is written in English, the abstract should be typed in English only. The abstract should be typed as concisely as possible and should be composed of: problem statement, method, scientific finding results, and short conclusion. The abstract should only be typed in one paragraph and one-column format.